Antiglitches in accreting pulsars from superfluid vortex avalanches. Issue 1 (20th May 2022) - Howitt, G; Melatos, A
ABSTRACT: Three sudden spin-down events, termed 'antiglitches', were recently discovered in the accreting pulsar NGC 300 ULX-1 by the Neutron Star Interior Composition Explorer mission. Unlike previous antiglitches detected in decelerating magnetars, these are the first antiglitches recorded in an accelerating pulsar. One standard theory is that pulsar spin-up glitches are caused by avalanches of collectively unpinning vortices that transfer angular momentum from the superfluid interior to the crust of a neutron star. Here, we test whether vortex avalanches are also consistent with the antiglitches in NGC 300 ULX-1, with the angular momentum transfer reversed. We perform N -body simulations of up to 5 × 10 3 pinned vortices in two dimensions in secularly accelerating and decelerating containers. Vortex avalanches routinely occur in both scenarios, propagating inwards and outwards, respectively. The implications for observables, such as size and waiting time statistics, are considered briefly.